White-Collar Crime in the Shadow Economy Lack of Detection, Investigation and Conviction Compared to Social Security Fraud - Gottschalk, Petter (Springer Nature, 2018)
convenience theory; financial crime; risk; crime prevention; fraud; organised crime; police investigation; social security; Shadow Economy; detection; investigation; convictions; prosecution; tip of the iceberg; police resources; crime detection theory